2012
DOI: 10.1103/physrevb.86.100507
|View full text |Cite
|
Sign up to set email alerts
|

Possible pairing symmetries in SrPtAs with a local lack of inversion center

Abstract: We discuss possible pairing symmetries in the hexagonal pnictide superconductor SrPtAs. The local lack of inversion symmetry of the two distinct conducting layers in the unit cell results in a special spin-orbit coupling with a staggered structure. We classify the pairing symmetry by the global crystal point group D 3d , and suggest some candidates for the stable state using a tight-binding model with an in-plane, density-density type pairing interaction. We may have some unconventional states like s + f -wave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 22 publications
2
91
3
Order By: Relevance
“…This is in general agreement with the LDA calculations, 15 that predict 74%. 5 The line node order parameter produces a much flatter curve (see Fig. 3, brown curve) than our data and a rather instant decrease, which does not match to our findings.…”
Section: Nuclear Relaxation Ratecontrasting
confidence: 56%
See 3 more Smart Citations
“…This is in general agreement with the LDA calculations, 15 that predict 74%. 5 The line node order parameter produces a much flatter curve (see Fig. 3, brown curve) than our data and a rather instant decrease, which does not match to our findings.…”
Section: Nuclear Relaxation Ratecontrasting
confidence: 56%
“…It is interesting how theoretical predictions, in particular for the chiral d-wave state 5,7 and the f -wave state 5,8 , compare with the present NQR study. With the knowledge of the bandstructure and a simple representation of the chiral d-wave state and the f -wave state provided by Ref.…”
Section: Nuclear Relaxation Ratementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, recent muon spin-rotation (µSR) experiments have revealed that time-reversal symmetry is broken at T c [172] and several experiments have reported a lack of nodes in the quasiparticle spectrum [172,173], all consistent with a chiral d-wave state. Due to layer stacking, the point group is reduced to D 3d in SrPtAs and the crystal structure also lacks local inversion symmetry, although the unit cell possesses a global inversion center [171,174]. The Fermi surface in SrPtAs consists of both two hole pockets around Γ and electron pockets at K, K [175].…”
Section: Srptasmentioning
confidence: 99%